Barbiturate AEDS, EEG and Cognitive Performance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Neuropsychological performance and quantitative EEGs were studied in 11 epileptic children, aged 7 to 14 years, both during treatment and without phenobarbital and mephobarbital, and in comparison to 13 matched controls, at Tulane University Medical School, New Orleans, LA.